THE EDUCATION OF CHILDREN UNDER THREE YEARS OF AGE IN THE SUMMIT OF THE AMERICAS: A RIGHT OR A FAVOR? - Rosânia Campos (Editora da Universidade de Santa Cruz do Sul, 2008)
This text aims to discuss the indications for child education present in the Inter-American Program for Education under the coordination of the Summit of the Americas. For that purpose, analytical reference to Roger Dale's policies was used and the studies of Shiroma, Campos, and Garcia (2004) were engaged as a methodology for the analysis of documents. Our analyses showed a twofold way for the organization of child education, that is, a curriculum for children under three years of age and another for the education of children aged closer to compulsory education. The curriculum for children under three is organized from two perspectives: the idea of educating their families - promoting child development and the idea of assistance - education oriented to health and nutrition. The lines of action are articulated from two poles: compensatory policies and vulnerable population. When contemplating child education following these perspectives, the Inter-American Program takes it away from the law sphere and ratifies curriculum concepts historically discussed in the area.